Re-apprehending misapprehensions: a practice for disclosing troubles in understanding in talk-in-interaction - Smith, MS; Seuren, LM (Elsevier, 2022)
The potential for misunderstanding is ever-present in interaction, making it necessary that interactants have means for identifying and remediating troubles in understanding should they appear. These include not only practices for remediating others’ misunderstandings, but also for remediating one's own misunderstandings. Using English and Dutch data, we analyse a practice that participants use for remediating misapprehensions on their part of some prior talk or given state-of-affairs, where the speaker first indexes a change-of-state and then explicates their misapprehension with "I thought (that) X" or "ik dacht dat X". In doing so the speakers disclose themselves to have misapprehended some talk or state-of-affairs and by so doing 're-apprehended' the 'actual' talk or 'correct' state-of-affairs, while also accounting for any action or conduct predicated on that misapprehension.